2023
DOI: 10.1039/d3mh00198a
|View full text |Cite
|
Sign up to set email alerts
|

A novel bilayer heterogeneous poly(ionic liquid) electrolyte for high-performance flexible supercapacitors with ultraslow self-discharge

Abstract: Flexible supercapacitors with high power density and long cyclic stability represent a promising candidate to be used as power supplies for portable electronics, but often suffer from the limited working...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In addition to their excellent applications in lithium-ion devices, polyionic liquids, which combine many advantages such as excellent thermodynamic properties and a wide potential window with low vapor pressure, are also a promising polymer gel electrolyte for high-performance flexible supercapacitors. A new bilayered nonhomogeneous polyionic liquid electrolyte (BHPE) has been designed by Dong et al 226 As shown in Fig. 50a, the BHPE consists of a layer of polyanionic complex of poly[1-ethyl-3-methylimidazolium(3-sulfopropyl)methacrylate] (PES) and a layer of polycationic complex of poly[2-(methacryloyloxy)ethyl]trimethylammonium bis(trifluoromethylsulfonyl)imide (PMT) synthesized by free radical polymerization.…”
Section: Applicationmentioning
confidence: 99%
“…In addition to their excellent applications in lithium-ion devices, polyionic liquids, which combine many advantages such as excellent thermodynamic properties and a wide potential window with low vapor pressure, are also a promising polymer gel electrolyte for high-performance flexible supercapacitors. A new bilayered nonhomogeneous polyionic liquid electrolyte (BHPE) has been designed by Dong et al 226 As shown in Fig. 50a, the BHPE consists of a layer of polyanionic complex of poly[1-ethyl-3-methylimidazolium(3-sulfopropyl)methacrylate] (PES) and a layer of polycationic complex of poly[2-(methacryloyloxy)ethyl]trimethylammonium bis(trifluoromethylsulfonyl)imide (PMT) synthesized by free radical polymerization.…”
Section: Applicationmentioning
confidence: 99%